Malpractice in Abortus Provocatus in Makassar City: A Study of Sadd al-Dzari’ah as a Preventive Measure of Medical Crimes - Fatra, Meyhira Fatrizia; Hasan, Hamzah; Fatmawati, Fatmawati (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The problem in this research is how the practice of abortion independently occurs without the presence of medical personnel in Makassar. Problem and Mudharat Perspective, the main problem is then divided into several sub-problems, namely: (1) What are the facts about the malpractice of abortion provoctus criminalis that occurs in Makassar. (2) What is the Makassar Court’s decision regarding the verdict of the perpetrators of abortion provocatus malpractice. (3) What are the Maslahah and Mudharat Aspects of Criminal Abortus Provocatus in Makassar. This type of research is carried out using a quantitative approach known as field research. The data sources in this research include primary sources and secondary data including data obtained through field research. Furthermore, the data collection methods used in field research (Field Research) involve observation, interviews and documentation methods. With this field research to investigate the factors that influence the abortion phenomenon in the context of Makassar City. The research population consisted of individuals who had experience of having an abortion in Makassar City. The results of this research are that Malprakti abortion provocatus is a crime in the city of Makassar by carrying out abortions individually and is proven to have carried out illegal practices asking for help from a traditional birth attendant without any medical assistance. Several cases of abortion malpractice perpetrators in Makassar have been proven to have committed the crime of abortion. Comparing the benefits and harms of abortion, the harm of abortions that occur in Makassar is greater because it is carried out illegally. The implication of the results of this research is that in terms of medical health, women have health risks related to unsafe abortion, such as infection, bleeding and long-term complications. There is a need for stricter law enforcement against illegal abortion practices and strengthening legal protection for women’s reproductive rights. The stigma and support faced by women who have abortions is important for emotional support and increasing health awareness regarding abortion services.